2002
DOI: 10.1016/s0169-5150(02)00075-0
|View full text |Cite
|
Sign up to set email alerts
|

Location and uptake: integrated household and GIS analysis of technology adoption and land use, with application to smallholder dairy farms in Kenya

Abstract: CIS-derived measures of location and space have increasingly been used in models of land use and ecology. However, they have made few inroads into the literature on technology adoption in developing countries, which continues to rely mainly on survey-derived information. Location, with all its dimensions of market access, demographics and agro-climate, nevertheless remains key to understanding potential for technology use. The measures of location typically used in the adoption literature, such as locational d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 26 publications
5
93
3
8
Order By: Relevance
“…About 46.1% farmers were small land holding and 35.6% were medium (< 1 ha) and there had insignificant association between land size and adoption of dairy. The finding is contrary to the study of Staal et al (2002), which found a positive correlation between these two qualitative variables. Only 15 percent farmer's main source of income was dairy farming, 14 percent farmers received credit and 11 percent farmers received extension services (Table 1).…”
Section: Farm Household Characteristicscontrasting
confidence: 99%
“…About 46.1% farmers were small land holding and 35.6% were medium (< 1 ha) and there had insignificant association between land size and adoption of dairy. The finding is contrary to the study of Staal et al (2002), which found a positive correlation between these two qualitative variables. Only 15 percent farmer's main source of income was dairy farming, 14 percent farmers received credit and 11 percent farmers received extension services (Table 1).…”
Section: Farm Household Characteristicscontrasting
confidence: 99%
“…In this case, farmer i adopts a certain technology if the derived benef its B i are higher that a certain threshold T (Staal et al, 2002):…”
Section: Economics Intensification and Technology Adoptionmentioning
confidence: 99%
“…These technologies could be clearly identified with a pathway of dairy intensification. The explanatory variables were selected based on previous studies on factors influencing technology adoption and development pathways (Nicholson et al, 1999;Staal et al, 2002, Baltenweck et al, 2003Pender, 2004). These variables included: distance of farm to the nearest populated area as indicator of location and access to markets; level of education of farmer and age of farmer representing characteristics of the household head in relation to management capacity; size of farm land and herd size because it was considered that technological development could be scale dependent; level of technical assistance because it was considered that information and advise can facilitate technology adoption; and finally family income considering that economic position of the household influences the possibility of technological investments.…”
Section: Economics Intensification and Technology Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The legumes were promoted because of their biological characteristics without taking account of the bio-physical and socio-economic factors that limited their adoption (Sumberg, 2002). Recent methods for analyzing smallholder systems and applying the innovation systems approach largely overcome these deficiencies and planted forage technologies can be targeted more effectively (Staal et al, 2002;Ouma et al, 2007;Tesfaye Lemma Tefera et al, 2010). See also for example fodder innovation research -Chapter 11.…”
Section: What Do We Know?mentioning
confidence: 99%